How We Came to Be: Inquiring into Teacher Identity Construction of Indonesian ELT Graduate Students - Refi Aksep Sativa; Isti Siti Saleha Gandana; Dinovia Fannil Kher (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
This study investigated the professional identity construction of two Indonesian English teachers pursuing a Master’s degree in ELT. Framed within Yazan’s (2018) sociocultural theory of language teacher identity, the research examined how critical incidents and significant moments shape the participants' trajectories in English language teaching. By utilizing narrative inquiry, this study offers nuanced insights into the evolving professional identities of ELT graduate students, emphasizing the interplay between personal experiences and professional development. The findings contribute to a deeper understanding of teacher identity formation in the Indonesian context, highlighting its inherent complexity and fluidity.